Multidisciplinary chronostratigraphic calibration of the Jurassic - Cretaceous transition in the Neuquén Basin - Kietzmann, Diego Alejandro (2017)
Detailed systematic studies are being carried out in the Vaca Muerta Formation in order to achieve an integrated multisisciplinary calibration of the jurassic/Cretaceous transition in the Neuquén Basin. Although this unit has a very well established ammonite biostratigraphy, the temporal distribution of biosonesis is yet a matter of hot debate. In this contribution we present the results of a well constrained integrated data form the Arroyo Loncoche section (spouthern Mendoza), where comprehensive cyclostratigraphic, paleomagnetic and biostratigraphic sampling/data allowed us to elaborate a very strong chronostratigraphic scheme for the Tithonian - Berriasian interval.